Experimental Evidence on the Compaction of Binary Granular Assemblies: Influence of Equivalent Intergranular Void Ratio - Y. Mahmoudi; A. C.Taiba; K. Doumi; L. Hazout; M. Belkhatir; W. Baille (Algerian Journal of Research and Technology (AJRT), 2020)
The assessment of compaction technique of soils is of vital importance in numerous geotechnical engineering constructions such as highways, airports, earth dams and other structures. Evaluation of affected parameters on this technique remains a major challenge in geotechnical engineering. For this context, this laboratory study presents the influence of the low plastic fines fraction on the compaction of sand-silt mixtures. The samples were reconstituted with fines content ranging from 0% to 30%. The soil samples were tested by compaction apparatus. A series of compaction tests were performed on different reconstituted sand-silt mixture samples to study the compaction characteristics of the two sand named as Chlef clean sand “CCS” and Chlef fine sand “CFS” mixed with low plastic Chlef silt “Ip=5%”) using the concept of the equivalent intergranular void ratio (e*). The test results show that the values of the maximum dry density increase with the increase of fines content for both tested materials (Chlef clean sand-silt mixtures and Chlef fine sand-silt mixtures) under consideration. Moreover, the obtained data indicate that the equivalent intergranular void ratio appears as a suitable parameter for prediction the compaction of different graded sand-silt mixtures for the tested low plastic Chlef fines ranging from (Fc=0% to Fc=30%) under study.